If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2=9x^2-2
We move all terms to the left:
2-(9x^2-2)=0
We get rid of parentheses
-9x^2+2+2=0
We add all the numbers together, and all the variables
-9x^2+4=0
a = -9; b = 0; c = +4;
Δ = b2-4ac
Δ = 02-4·(-9)·4
Δ = 144
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{144}=12$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-12}{2*-9}=\frac{-12}{-18} =2/3 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+12}{2*-9}=\frac{12}{-18} =-2/3 $
| 18=9(x+80 | | 1/2x+6=1/4+4 | | 2(5c-17)-4=3(c+2)+26 | | 4-4x=-35 | | 152x+9=17 | | 5(x-1)=2x+17 | | h-11=1 | | 2(3x-4)-(6-2x)=3(x+2) | | -3x-6=4x-48 | | (4x-1)/2=2x-7 | | 6x-7=9x-31 | | 9d-17=3d+13 | | 4x+15=33-25+5x | | 8-2p=-14 | | 4y=4.5 | | 5x+6-x=20+2x | | 6r-50=46-2r | | 4(x+5)=15x+ | | 2l-4=18 | | 3(3c-4)=49 | | x=x+6=-8 | | x-x+56=-8 | | 2(3c-4)=40 | | e-6=9-2e | | ;16=8(x+9) | | 16=8(x+9( | | 2v+5=-19 | | (2x-4(/5=4 | | 8r-13=4r+7 | | -3(-2x-1)=6x+3 | | 3-8k=-5 | | 10x–7=73 |